Bone cement based on nano microcrystalline cellulose silver-loaded filler as well as preparation method and application of bone cement
By using nano-microcrystalline cellulose silver-loaded fillers and photoinitiators in bone cement, the problem of bone cement-based repair materials generating polymerization heat and shrinkage during the curing process is solved, achieving efficient anti-shrinkage properties and being suitable for 3D printing. Effect.
Patent Information
- Application Number
- CN202411437100.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-17
AI Technical Summary
Existing bone cement-based restoration materials generate a large amount of polymerization heat and severe shrinkage during the curing process, resulting in reduced accuracy and inability to apply to 3D printing.
Nano-microcrystalline cellulose silver-loaded filler is used as a component of bone cement. The nano-filler is uniformly dispersed through ultrasonic treatment, and a photoinitiator is used to replace the self-curing agent to reduce the generation of polymerization heat.
It improves the anti-shrinkage performance of bone cement, reduces the shrinkage rate after curing, enhances the antibacterial and antibacterial properties of bone cement, and makes it suitable for 3D printing technology, achieving personalized and precise preparation of restorations.
Smart Images

Figure CN119318739A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial prosthesis preparation, and in particular to a bone cement based on nano-microcrystalline cellulose silver-loaded filler, and a preparation method and application thereof. Background Art
[0002] As people age, the elasticity and toughness of human bones decrease, and cartilage becomes thinner, so the ability to restore, repair and rebuild the connection with cartilage becomes increasingly poor, and eventually the disease develops into osteoarthritis. Osteoarthritis patients may experience joint pain, limited mobility and joint deformities. At the same time, as people age, bone density decreases rapidly, which can easily cause bone fractures and cracks. As a result, bone diseases, fractures and breakages have become one of the main factors affecting the health of the elderly. In recent years, the concept of healthy aging has received increasing attention from the international community. Using artificial prostheses to replace damaged or diseased bones, joints and other parts of the human body is an effective way to relieve patients' pain.
[0003] For example, artificial skull prostheses include metal prostheses (titanium mesh plates) and non-metal prostheses (polyetheretherketone (PEEK), polymethyl methacrylate (PMMA)). Among them, the titanium mesh plate adopts a covering repair with a thickness of less than 1 mm. It is difficult to meet the biomechanical requirements after implantation into the skull, especially the stress shielding at the interface between metal and bone will lead to surrounding bone loss. And this method cannot match the shape of the patient's skull and cannot be customized. Although PEEK has good biocompatibility, wear resistance, stable chemical properties, strong plasticity, elasticity and strength comparable to autologous skull, the cost of PEEK material itself is relatively high, and the cost of PEEK personalized skull prepared by 3D printing is even higher, which limits its application. PMMA bone cement is a traditional skull repair material with a wide range of clinical applications. It has good fluidity in the early stages of curing and can be injected. However, the injected PMMA bone cement tends to generate a large amount of polymerization heat when curing in situ at the defect site, which can easily cause brain edema. After curing, the polymer shrinks severely, affecting its accuracy. In addition, due to its own thermosetting properties, it cannot be 3D printed, and cannot be personalized and precise.
[0004] Commercial bone cement spacers are of a single type and lack joint surface matching. Bone cement spacers hand-made by doctors based on clinical experience cannot accurately determine the shape and size of the bone cement spacers, resulting in poor joint fit.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing a nano-microcrystalline cellulose silver-loaded filler. The prepared nano-microcrystalline cellulose silver-loaded filler can be used to prepare bone cement, improve the anti-shrinkage performance of bone cement, and at least solve one of the technical problems existing in the prior art that bone cement-based repair materials generate a large amount of polymerization heat and shrink severely, and cannot be used for 3D printing.
[0007] The second object of the present invention is to provide a nano-microcrystalline cellulose silver-loaded filler.
[0008] A third object of the present invention is to provide a bone cement for 3D printing.
[0009] A fourth object of the present invention is to provide a method for preparing bone cement for 3D printing.
[0010] A fifth object of the present invention is to provide the use of the above-mentioned bone cement or the bone cement prepared by the above-mentioned preparation method in the preparation of bone cement-based restorations.
[0011] The sixth object of the invention is to provide a method for preparing a personalized bone cement-based restoration.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] In a first aspect, the present invention provides a method for preparing a nano-microcrystalline cellulose silver-loaded filler, comprising the following steps:
[0014] A1. Pre-treating microcrystalline cellulose by adding it into an acid solution to obtain a microcrystalline cellulose dispersion, dialyzing the microcrystalline cellulose dispersion, and freeze-drying the dialyzate to obtain nano-microcrystalline cellulose;
[0015] A2. Add nano-microcrystalline cellulose to the dopamine solution, mix well, slowly add the silver ammonia solution, add an excess amount of reducing agent, and stir to obtain the nano-microcrystalline cellulose silver-loaded filler.
[0016] Further, the amount of microcrystalline cellulose added is 4 to 6 g of microcrystalline cellulose per 40 to 50 ml of acid solution, preferably 5 g of microcrystalline cellulose per 45 ml of acid solution;
[0017] Preferably, the concentration of the acid solution is 50-80wt.%, preferably 65wt.%;
[0018] Preferably, the acid solution comprises an aqueous solution of sulfuric acid, hydrochloric acid, acetic acid, citric acid or nitric acid;
[0019] Preferably, the pretreatment comprises reacting at a temperature of 50 to 60°C for 3 to 7 hours, preferably at 55°C for 5 hours;
[0020] Preferably, the pretreatment further comprises adding distilled water after the reaction until the pH of the solution is neutral, and then cooling and ultrasonicating to obtain a microcrystalline cellulose dispersion;
[0021] Preferably, the ultrasonic conditions include ultrasonication at a power of 230 to 280 W for 12 to 18 min; preferably ultrasonication at a power of 250 W for 15 min;
[0022] Preferably, the pretreatment further comprises centrifuging to remove the supernatant, and washing the precipitate with distilled water 2 to 3 times;
[0023] Preferably, the centrifugation condition is 3000 rpm to 6500 rpm for 5 to 30 min, preferably 5000 rpm for 5 to 30 min;
[0024] Preferably, the dialysis comprises dialysis until the pH of the dialysate is neutral;
[0025] Preferably, the pore size of the dialysis membrane is 3500-7000Da, preferably 3500Da;
[0026] Preferably, the freeze-drying temperature is -30 to 0°C, preferably -20°C.
[0027] Furthermore, the mixing ratio of the nano-microcrystalline cellulose to the dopamine solution is 0.5 to 5:100 (w / v);
[0028] Preferably, the dopamine solution is prepared by adding dopamine hydrochloride into a buffer solution;
[0029] Preferably, the concentration of dopamine hydrochloride is 1 to 5 mg / ml, preferably 2 mg / mL;
[0030] Preferably, the buffer is Tris-HCl buffer or PBS buffer;
[0031] Preferably, the volume ratio of the amount of the added silver ammonia solution to the dopamine solution is 0.5 to 3:100, preferably 1:100;
[0032] Preferably, the silver ammonia solution is prepared by slowly adding concentrated ammonia water to a silver nitrate solution;
[0033] Preferably, the concentration of the silver nitrate solution is 5 to 30 mM, preferably 10 mM;
[0034] Preferably, the reducing agent comprises glucose, ascorbic acid or citric acid, preferably glucose;
[0035] Preferably, the stirring time is 6 to 10 hours, preferably 8 hours.
[0036] In a second aspect, the present invention provides a nano-microcrystalline cellulose silver-loaded filler, which is prepared by the above-mentioned preparation method.
[0037] In a third aspect, the present invention provides a bone cement for 3D printing, comprising the following components in percentage by mass:
[0038]
[0039] Nano-microcrystalline cellulose silver-loaded filler 0.05-0.3%;
[0040] The nano-microcrystalline cellulose silver-loaded filler is prepared by the above-mentioned preparation method.
[0041] Further, the photoinitiator includes photoinitiator 819, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or acylphosphonic acid lithium salt;
[0042] Preferably,
[0043] The diluent includes methyl methacrylate, bisphenol A acrylate or glycerol trimethyl acrylate;
[0044] Preferably, the cross-linking agent is ethylene glycol dimethacrylate;
[0045] Preferably, the stabilizer is butylated hydroxytoluene;
[0046] Preferably, the developer is barium sulfate.
[0047] In a fourth aspect, the present invention provides a method for preparing the above-mentioned bone cement, comprising the following steps:
[0048] B1, sequentially mixing polymethyl methacrylate, a photoinitiator, a diluent, a crosslinking agent, a stabilizer and a developer to obtain a preliminary mixture;
[0049] B2, adding nano-microcrystalline cellulose silver-loaded filler to the preliminary mixture, and obtaining bone cement by ultrasonication;
[0050] Preferably, the ultrasonic treatment conditions include 280-320W ultrasonic treatment for 25-35 min, preferably 300W ultrasonic treatment for 30 min.
[0051] In a fifth aspect, the present invention provides the use of the above-mentioned bone cement or the bone cement prepared by the above-mentioned preparation method in the preparation of a bone cement-based restoration;
[0052] Preferably, the bone cement restoration comprises a restoration of a damaged or diseased bone or joint.
[0053] In a sixth aspect, the present invention provides a method for preparing a personalized bone cement-based prosthesis, comprising the following steps:
[0054] C1. Establish a visual 3D negative model based on the data of the part to be repaired;
[0055] C2. Use the above-mentioned bone cement or the bone cement prepared by the above-mentioned preparation method to perform 3D printing according to the visualized three-dimensional model negative mold to obtain a personalized bone cement-based restoration.
[0056] Furthermore, the step C1 comprises the following steps:
[0057] C11. Perform CT scan or MR scan on the part to be repaired to obtain scan data;
[0058] C12. Calculate the medical morphology of the part to be repaired by interactive medical image control system software, and obtain a visualized three-dimensional model of the part to be repaired;
[0059] C13, obtaining a negative model of the visualized three-dimensional model of the part to be repaired according to the visualized three-dimensional model CT of the part to be repaired;
[0060] Preferably, the layer thickness of the scan data is ≤1 mm, preferably 0.1 to 0.3 mm;
[0061] Preferably, the inner surface of the female mold of the visualized three-dimensional model is provided with concave and convex patterns with a depth of 0.1 to 1.5 mm;
[0062] Preferably, after step C12, the step further includes comparing the visualized three-dimensional model of the part to be repaired with the visualized three-dimensional model of the opposite side of the part to be repaired, and if there is asymmetry, making corrections according to the visualized three-dimensional model of the opposite side of the part to be repaired;
[0063] Preferably, the initiating light wavelength of the 3D printing is 350-450nm, preferably 405nm;
[0064] Preferably, the triggering light intensity of the 3D printing is 150-230 mW / cm 2 , preferably 200mW / cm 2 ;
[0065] Preferably, the moving speed of the blue light generator for 3D printing is 5 to 15 mm / min, preferably 10 mm / min;
[0066] Preferably, the thickness of the printing layer of the 3D printing is 60-110 μm, preferably 100 μm;
[0067] Preferably, the step B2 further includes secondary curing and cleaning and drying;
[0068] Preferably, the secondary curing comprises ultraviolet light irradiation for 10 to 20 minutes;
[0069] Preferably, the power of the ultraviolet light irradiation is 90-120 mW / cm 2 , preferably 100 mW / cm 2 ;
[0070] Preferably, the cleaning comprises cleaning the surface using an organic solvent;
[0071] Preferably, the organic solvent comprises ethanol solution, acetone or ethylene glycol diacetate.
[0072] The invention provides a method for preparing a nano-microcrystalline cellulose silver-loaded filler. Compared with the prior art, the microcrystalline cellulose modified by an acid solution is dialyzed to stabilize the pH of its dialysate to be neutral; the dialysis is followed by freeze drying for nano-crystalization to remove excess solution, thereby obtaining fluffy white nano-microcrystalline cellulose; a dopamine solution is then applied for further modification to prepare a nano-microcrystalline cellulose silver-loaded filler, which is used in the preparation of bone cement to improve the anti-shrinkage performance of the bone cement, thereby solving the technical problem that the polymer shrinks severely after the bone cement is solidified, thereby affecting its accuracy.
[0073] On the other hand, the bone cement for 3D printing provided uses a photoinitiator instead of a self-curing agent to avoid the bone cement from easily generating a large amount of polymerization heat, and can be used for 3D printing; by adding nano-microcrystalline cellulose silver filler, the shrinkage rate of the bone cement after curing can be reduced, and the shrinkage resistance of the bone cement can be improved. It can be used to prepare bone cement-based restorations, and a visual three-dimensional model negative mold is established based on the data of the part to be repaired, and combined with 3D printing technology, the preparation of irregular restorations is realized, and the matching degree between the restoration and the part to be repaired is improved. The technical problem that the bone cement-based repair materials in the prior art generate a large amount of polymerization heat and shrink severely, and cannot be used for 3D printing is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0075] Figure 1 This is a comparison chart of the in vitro antibacterial performance test of different bone cements provided in Experiment 3 of the present invention. DETAILED DESCRIPTION
[0076] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0077] The methods and techniques of the present invention are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.
[0078] The present invention provides a method for preparing a nano-microcrystalline cellulose silver-loaded filler, comprising the following steps:
[0079] A1. Pre-treating microcrystalline cellulose by adding it into an acid solution to obtain a microcrystalline cellulose dispersion, dialyzing the microcrystalline cellulose dispersion, and freeze-drying the dialyzate to obtain nano-microcrystalline cellulose;
[0080] A2. Add nano-microcrystalline cellulose to the dopamine solution, mix well, slowly add the silver ammonia solution, add an excess amount of reducing agent, and stir to obtain the nano-microcrystalline cellulose silver-loaded filler.
[0081] Compared with the prior art, the pH value of the dialysate of the microcrystalline cellulose modified by the acid solution is stabilized to be neutral by dialyzing; the excess solution is removed by freeze drying after dialysis to obtain fluffy white nano-microcrystalline cellulose, which is further modified by applying dopamine solution to prepare nano-microcrystalline cellulose silver-loaded filler, which can be used in the preparation of bone cement to improve the anti-shrinkage performance of bone cement, and solve the technical problem that the polymer shrinks severely after the bone cement is solidified, affecting its accuracy.
[0082] In some specific embodiments, the amount of microcrystalline cellulose added is 4 to 6 g of microcrystalline cellulose per 40 to 50 ml of acid solution, preferably 5 g of microcrystalline cellulose per 45 ml of acid solution.
[0083] Among them, the concentration of the acid solution is 50-80wt.%, and the acid solution includes an aqueous solution of sulfuric acid, hydrochloric acid, acetic acid, citric acid or nitric acid; it is further proved that the preferred concentration of sulfuric acid aqueous solution is 65wt.%, which can effectively play the role of acidic hydrolysis of cellulose.
[0084] In some specific embodiments, the pretreatment comprises reacting at a temperature of 50 to 60° C. for 3 to 7 hours, preferably at 55° C. for 5 hours;
[0085] The reaction can be terminated by adding distilled water until the pH of the solution is neutral after the reaction, and then the microcrystalline cellulose dispersion is obtained by ultrasonication after cooling. The ultrasonication conditions include ultrasonication at a power of 230 to 280 W for 12 to 18 minutes; preferably, ultrasonication at a power of 250 W for 15 minutes;
[0086] In some specific embodiments, the pretreatment further comprises centrifuging to remove the supernatant and washing the precipitate with distilled water for 2 to 3 times.
[0087] The acid solution is removed by washing with distilled water, wherein the centrifugation condition is 3000 rpm to 6500 rpm for 5 to 30 min, preferably 5000 rpm for 5 to 30 min;
[0088] In some specific embodiments, the dialysis comprises dialysis until the pH of the dialysate is neutral.
[0089] Wherein, the pore size of the dialysis membrane is 3500-7000Da, preferably 3500Da;
[0090] In some specific embodiments, the freeze-drying temperature is -30 to 0°C.
[0091] The freeze-drying temperature may be, but is not limited to, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C or 0°C, and may be any temperature between -30 and 0°C, preferably -20°C.
[0092] In some specific embodiments, the mixing ratio of the nano-microcrystalline cellulose to the dopamine solution is 0.5-5:100 (w / v), preferably 1:100.
[0093] The dopamine solution is prepared by adding dopamine hydrochloride into a buffer solution; the concentration of dopamine hydrochloride in the dopamine solution is 1-5 mg / ml, preferably 2 mg / mL, and the buffer solution is Tris-HCl buffer solution or PBS buffer solution.
[0094] In some specific embodiments, the volume ratio of the added silver ammonia solution to the dopamine solution is 0.5-3:100, preferably 1:100; wherein the silver ammonia solution is prepared by slowly adding concentrated ammonia water to a silver nitrate solution; the concentration of the silver nitrate solution used is 5-30mM, preferably 10mM.
[0095] In some specific embodiments, the reducing agent can reduce silver ions to silver nanoparticles, and the reducing agent can be selected from glucose, ascorbic acid or citric acid, preferably glucose;
[0096] In some specific embodiments, the stirring time is 6 to 10 hours, preferably 8 hours.
[0097] According to another aspect of the present invention, there is also provided a nano-microcrystalline cellulose silver-loaded filler, which is prepared by the above-mentioned preparation method.
[0098] According to another aspect of the present invention, there is also provided a bone cement for 3D printing, comprising the following components in mass percentage:
[0099]
[0100] Nano-microcrystalline cellulose silver-loaded filler 0.05-0.3%;
[0101] The nano-microcrystalline cellulose silver-loaded filler is prepared by the above-mentioned preparation method.
[0102] The use of photoinitiators instead of self-curing agents can prevent bone cement from easily generating a large amount of polymerization heat, and can be used for 3D printing; by adding nano-microcrystalline cellulose silver filler, the shrinkage rate of bone cement after curing can be reduced, and the anti-shrinkage performance of bone cement can be improved. It can be used to prepare bone cement-based restorations, improve the accuracy and matching of the restorations, and solve the technical problems in the prior art that bone cement-based repair materials generate a large amount of polymerization heat and shrink severely, and cannot be used for 3D printing.
[0103] In some specific embodiments, the photoinitiator includes photoinitiator 819, TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide) or LAP (lithium acylphosphonate).
[0104] In some specific embodiments, the diluent includes methyl methacrylate, bisphenol A acrylate or glycerol trimethyl acrylate.
[0105] In some specific embodiments, the cross-linking agent is ethylene glycol dimethacrylate.
[0106] In some specific embodiments, the stabilizer is butylated hydroxytoluene.
[0107] In some specific embodiments, the developer is barium sulfate.
[0108] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned bone cement, comprising the following steps:
[0109] B1, sequentially mixing polymethyl methacrylate, a photoinitiator, a diluent, a crosslinking agent, a stabilizer and a developer to obtain a preliminary mixture;
[0110] B2. Add nano-microcrystalline cellulose silver-loaded filler into the preliminary mixture and obtain bone cement by ultrasound.
[0111] Compared with the method in the prior art that uses ethanol as a medium to introduce fillers into the matrix, the nano-microcrystalline cellulose silver-loaded filler is evenly dispersed into the preliminary mixture through ultrasonic action, which can avoid the influence of ethanol volatilization on the microstructure of bone cement, improve the overall anti-shrinkage performance of bone cement, reduce the shrinkage rate after curing, and improve the antibacterial and antimicrobial properties through the action of silver ions.
[0112] In some specific embodiments, the ultrasonic treatment conditions include 280-320W ultrasonic treatment for 25-35 min, preferably 300W ultrasonic treatment for 30 min.
[0113] According to another aspect of the present invention, there is also provided the use of the above-mentioned bone cement or the bone cement prepared by the above-mentioned preparation method in preparing a bone cement-based restoration.
[0114] Among them, bone cement restorations include bone or joint restorations due to human body damage or disease.
[0115] According to another aspect of the present invention, there is also provided a method for preparing a personalized bone cement-based restoration, comprising the following steps:
[0116] C1. Establish a visual 3D negative model based on the data of the part to be repaired;
[0117] C2. Use the above-mentioned bone cement or the bone cement prepared by the above-mentioned preparation method to perform 3D printing according to the visualized three-dimensional model negative mold to obtain a personalized bone cement-based restoration.
[0118] A visual three-dimensional negative model is established based on the data of the part to be repaired, and combined with 3D printing technology, the preparation of irregular restorations is realized, thereby improving the matching degree between the restoration and the part to be repaired.
[0119] In some specific embodiments, the step C1 comprises the following steps:
[0120] C11. Perform CT scan or MR scan on the part to be repaired to obtain scan data;
[0121] C12. Calculate the medical morphology of the part to be repaired by interactive medical image control system software, and obtain a visualized three-dimensional model of the part to be repaired;
[0122] C13. Obtain a negative model of the visualized three-dimensional model of the part to be repaired based on the visualized three-dimensional model CT of the part to be repaired.
[0123] Among them, CT or MR medical imaging technology is used to scan the patient's part to be repaired. The patient's scan data format can be DICOM or JPEG format. The patient's scan data is obtained and imported into the interactive medical image control system software. The part to be repaired is calculated by setting the image data threshold range, the patient's medical morphology is obtained, and a visual three-dimensional model of the part to be repaired is generated.
[0124] Preferably, the layer thickness of the scan data is ≤1 mm, preferably 0.1 to 0.3 mm;
[0125] Preferably, the inner surface of the female mold of the visualized three-dimensional model is provided with concave and convex patterns with a depth of 0.1 to 1.5 mm;
[0126] Preferably, after step C12, the step further includes comparing the visualized three-dimensional model of the part to be repaired with the visualized three-dimensional model of the opposite side of the part to be repaired, and if there is asymmetry, correcting it according to the visualized three-dimensional model of the opposite side of the part to be repaired.
[0127] Specifically, the complete scan data on the opposite side of the part to be repaired can be mirrored by a mirroring tool in CAD design software to obtain a visualized three-dimensional model of the opposite side of the part to be repaired for comparison; or the visualized three-dimensional model of the part to be repaired can be processed by a translation module, a rotation module, a smoothing module, a Bohr module, stretching, rotation, etc. to obtain a mirror model of the visualized three-dimensional model of the part to be repaired and compare it with the visualized three-dimensional model of the opposite side of the part to be repaired.
[0128] Preferably, the initiating light wavelength of the 3D printing is 350-450nm, preferably 405nm;
[0129] Preferably, the triggering light intensity of the 3D printing is 150-230 mW / cm 2 , preferably 200mW / cm 2 ;
[0130] Preferably, the moving speed of the blue light generator for 3D printing is 5 to 15 mm / min, preferably 10 mm / min;
[0131] Preferably, the thickness of the printing layer of the 3D printing is 60-110 μm, preferably 100 μm;
[0132] Preferably, the step B2 further includes secondary curing and cleaning and drying;
[0133] Preferably, the secondary curing comprises ultraviolet light irradiation for 10 to 20 minutes;
[0134] Preferably, the power of the ultraviolet light irradiation is 90-120 mW / cm 2 , preferably 100 mW / cm2 ;
[0135] Preferably, the cleaning comprises cleaning the surface using an organic solvent;
[0136] Preferably, the organic solvent comprises ethanol solution, acetone or ethylene glycol diacetate.
[0137] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0138] Example 1
[0139] A nano-microcrystalline cellulose silver-loaded filler is prepared according to the following steps:
[0140] 1. Weigh 5.0 g of microcrystalline cellulose into a round-bottom flask, then add 45 ml of 65wt.% sulfuric acid solution and stir in a 55°C water bath. Continue stirring for 5 hours after the addition is complete, then add a large amount of distilled water until the pH of the solution is about 5 to terminate the oxidation reaction. After cooling to room temperature, perform 250W power ultrasound for 15 minutes to disperse the sample, and remove the supernatant by centrifugation at 5000rpm. This process is repeated three times to purify the sample, and finally resuspend it with distilled water to obtain a purified dispersion. The purified dispersion is dialyzed in a 3500kDa dialysis bag until the pH of the dialysate reaches neutral. Finally, the dialysate is left to stand overnight at 4°C, and then freeze-dried at -20°C to obtain fluffy white nanocrystalline cellulose (CNCs).
[0141] 2. Weigh 1.2 g of Tirs and dissolve it in 50 ml of deionized water, then add 29.4 ml of 0.1 mol / L hydrochloric acid, adjust the pH to 8.5 and dilute to 200 ml to obtain Tris-HCl buffer. Dissolve 0.495 g of dopamine hydrochloride powder in 200 ml of Tris-HCl buffer to obtain a 2 mg / mL dopamine solution. Add concentrated ammonia water to the 10 mM AgNO3 solution until it turns brown, and continue to add until it is transparent and clear to obtain a silver ammonia solution. Mix CNCs with dopamine solution in a ratio of 1:100, slowly add silver ammonia solution and excess glucose, and stir for 8 hours to obtain CNCs loaded with silver nanoparticles.
[0142] Example 2
[0143] A nano-microcrystalline cellulose silver-loaded filler is prepared according to the following steps:
[0144] 1. Weigh 4 grams of microcrystalline cellulose into a round-bottom flask, add 40 ml of 80wt.% sulfuric acid solution and stir in a 50°C water bath. Continue stirring for 3 hours after the addition is complete, then add distilled water until the solution pH is about 5 to terminate the reaction. After cooling to room temperature, perform 230W power ultrasound for 18 minutes to disperse the sample, and remove the supernatant by centrifugation at 3000rpm. This process is repeated three times to purify the sample, and finally resuspend it with distilled water to obtain a purified dispersion. The purified dispersion is dialyzed in a 3500Da dialysis bag until the pH value of the dialysate reaches neutral. Finally, the dialysate is left to stand overnight at 4°C, and then freeze-dried at -30°C to obtain fluffy white nano-microcrystalline cellulose (CNCs).
[0145] 2. Weigh 1.2 g of Tirs and dissolve it in 50 ml of deionized water, then add 29.4 ml of 0.1 mol / L hydrochloric acid, adjust the pH to 8.5 and dilute to 200 ml to obtain Tris-HCl buffer. Dissolve 0.248 g of dopamine hydrochloride powder in 200 ml of Tris-HCl buffer to obtain a 1 mg / mL dopamine solution. Add concentrated ammonia water to 5 mM AgNO3 solution until it turns brown, and continue to add until it is transparent and clear to obtain a silver ammonia solution. Mix CNCs and dopamine solution in a ratio of 0.5:100, slowly add silver ammonia solution and excess glucose, and stir for 6 hours to obtain CNCs loaded with silver nanoparticles.
[0146] Example 3
[0147] A nano-microcrystalline cellulose silver-loaded filler is prepared according to the following steps:
[0148] 1. Weigh 6 grams of microcrystalline cellulose into a round-bottom flask, add 50 ml of 80wt.% sulfuric acid solution and stir in a 60°C water bath. Continue stirring for 7 hours after the addition is complete, then add distilled water until the solution pH is 5 to terminate the reaction. After cooling to room temperature, perform 280W power ultrasound for 18 minutes to disperse the sample, and remove the supernatant by centrifugation at 6500rpm. This process is repeated three times to purify the sample, and finally resuspend it with distilled water to obtain a purified dispersion. The purified dispersion is dialyzed in a 3500Da dialysis bag until the pH value of the dialysate reaches neutral. Finally, the dialysate is left to stand overnight at 4°C, and then freeze-dried at -10°C to obtain fluffy white nano-microcrystalline cellulose (CNCs).
[0149] 2. Weigh 1.2 g of Tirs and dissolve it in 50 ml of deionized water, then add 29.4 ml of 0.1 mol / L hydrochloric acid, adjust the pH to 8.5 and dilute to 200 ml to obtain Tris-HCl buffer. Dissolve 1.238 g of dopamine hydrochloride powder in 200 ml of Tris-HCl buffer to obtain a 5 mg / mL dopamine solution. Add concentrated ammonia water to 30 mM AgNO3 solution until it turns brown, and continue to add until it is transparent and clear to obtain a silver ammonia solution. Mix CNCs and dopamine solution in a ratio of 5:100, slowly add silver ammonia solution and excess glucose, and stir for 6 hours to obtain CNCs loaded with silver nanoparticles.
[0150] Comparative Example 1
[0151] Different from Example 1, the purified dispersion was not dialyzed, but directly left to stand overnight at 4°C, and then freeze-dried at -20°C, to finally obtain fluffy white nanocrystalline cellulose (CNCs).
[0152] Comparative Example 2
[0153] Different from Example 1, the dialysate is centrifuged to discard the supernatant, and then naturally dried to obtain treated microcrystalline cellulose (CNCs).
[0154] Comparative Example 3
[0155] Different from Example 1, the purified dispersion is centrifuged and the supernatant is discarded to obtain treated microcrystalline cellulose (CNCs).
[0156] Embodiments 4 to 6
[0157] A bone cement for 3D printing is prepared by using the nano-microcrystalline cellulose silver-loaded filler prepared in Examples 1 to 3, and specifically comprises the following components in percentage by mass: 87.5% of polymethyl methacrylate; 0.15% of photoinitiator 819; 3.6% of methyl methacrylate; 1.5% of ethylene glycol dimethacrylate; 0.15% of butylated hydroxytoluene; 7% of barium sulfate; and 0.1% of nano-microcrystalline cellulose silver-loaded filler.
[0158] The preparation was carried out according to the following operating steps: polymethyl methacrylate, photoinitiator 819, methyl methacrylate, ethylene glycol dimethacrylate, butylated hydroxytoluene and barium sulfate were mixed in proportion to obtain a preliminary mixture; nano-microcrystalline cellulose silver filler was added to the preliminary mixture, and ultrasonic treatment was performed using an ultrasonic disperser for 30 minutes at a power of 300 W to ensure that the nano-filler was evenly dispersed in the above mixture.
[0159] Comparative Examples 4 to 6
[0160] The difference from Example 4 is that the nano-microcrystalline cellulose silver-loaded fillers prepared in Comparative Examples 1 to 3 are respectively used to prepare bone cement.
[0161] Example 7
[0162] The difference from Example 4 is that the specific components include the following mass percentages: 86.6% polymethyl methacrylate; 0.4% TPO; 4% bisphenol A acrylate; 1.1% ethylene glycol dimethacrylate; 0.05% butylated hydroxytoluene; 8% barium sulfate; and 0.3% nano-microcrystalline cellulose silver-loaded filler.
[0163] The preparation is carried out according to the following operating steps: polymethyl methacrylate, TPO, bisphenol A acrylate 4, ethylene glycol dimethacrylate, butylated hydroxytoluene and barium sulfate are mixed in proportion to obtain a preliminary mixture; nano-microcrystalline cellulose silver filler is added to the preliminary mixture, and ultrasonic treatment is performed using an ultrasonic disperser for 30 minutes at a power of 300 W to ensure that the nano-filler is evenly dispersed in the above mixture.
[0164] Example 8
[0165] The difference from Example 4 is that the specific components include the following mass percentages: 89.25% polymethyl methacrylate; 0.25% LAP; 3.2% glycerol trimethyl acrylate; 2% ethylene glycol dimethacrylate; 0.3% butylated hydroxytoluene; 5% barium sulfate; and 0.05% nano-microcrystalline cellulose silver-loaded filler.
[0166] The preparation was carried out according to the following operating steps: polymethyl methacrylate, LAP, glycerol trimethyl acrylate, ethylene glycol dimethacrylate, butylated hydroxytoluene and barium sulfate were mixed in proportion to obtain a preliminary mixture; nano-microcrystalline cellulose silver filler was added to the preliminary mixture, and ultrasonic treatment was performed using an ultrasonic disperser for 30 minutes at a power of 300 W to ensure that the nano-filler was evenly dispersed in the above mixture.
[0167] Comparative Example 7
[0168] The difference from Example 4 is that the content of the photoinitiator is 0.08%.
[0169] Comparative Example 8
[0170] The difference from Example 4 is that the content of the photoinitiator is 0.45%.
[0171] Comparative Example 9
[0172] The difference from Example 4 is that the content of the silver-loaded nano-microcrystalline cellulose filler is 0.04%.
[0173] Comparative Example 10
[0174] The difference from Example 4 is that the content of the silver-loaded nano-microcrystalline cellulose filler is 0.35%.
[0175] Comparative Example 11
[0176] Different from Example 4, no nano-microcrystalline cellulose silver-loaded filler was added.
[0177] Test 1: Shrinkage resistance test
[0178] The anti-shrinkage performance of the bone cement prepared in Examples 4 to 8 and Comparative Examples 4 to 11 was tested using a rotational rheometer. The specific method is as follows: 5 mL of the bone cement in the above embodiments and comparative examples was weighed, the light intensity of the UV curing machine light source was adjusted to 5% in the light curing mode, the PP25 flat rotor was selected, the initial rotor gap was adjusted to 0.25 mm, the normal stress was adjusted to 0, and the shrinkage rate of the tested sample was obtained by the change in the flat plate gap of the bone cement as the exposure time was extended in the oscillation mode. The specific test results are shown in Table 1.
[0179] Test 2 Mechanical properties test
[0180] Corresponding mechanical property tests were performed with reference to the method of standard YY0459 2003: the compressive strength and flexural strength of the bone cements prepared in Examples 4 to 8 and Comparative Examples 4 to 11 were tested, and the specific results are shown in Table 1.
[0181] Table 1
[0182]
[0183]
[0184] As shown in Table 1, compared with Comparative Example 11, the shrinkage rates of Examples 4 to 8 are all reduced, and the addition of 0.05 to 0.3% nano-microcrystalline cellulose silver-loaded filler can improve the shrinkage resistance of bone cement;
[0185] Compared with Example 4, the shrinkage rate of Comparative Examples 4 to 6 increases, and the compressive strength and flexural strength decrease. It can be seen that in the process of preparing nano-microcrystalline cellulose silver-loaded filler, the steps of dialysis and freeze-drying can improve the anti-shrinkage ability of nano-microcrystalline cellulose silver-loaded filler in bone cement and enhance the mechanical properties. The difference between Comparative Example 7 and the embodiment is only the different content of photoinitiator. When the content of photoinitiator is reduced, the shrinkage rate will be reduced and the mechanical properties will be enhanced. Therefore, the shrinkage rate and mechanical properties are not much different from Example 4, but the polymerization rate of Comparative Example 7 is slowed down and the curing time is prolonged, which will lead to incomplete curing of bone cement under the existing 3D printing system, affecting its use. Due to the excessive amount of photoinitiator used in Comparative Example 8, its compressive strength and flexural strength are reduced, but the more photoinitiator content, the more free radicals are generated, resulting in an increase in the shrinkage rate of bone cement, so the shrinkage rate of Comparative Example 8 increases. It can be seen that controlling the photoinitiator content to 0.1-0.4 can improve the compression and bending resistance of bone cement, and keep the bone cement in good mechanical properties. The further increase of the photoinitiator content leads to a downward trend in the mechanical properties of bone cement, but further increasing the photoinitiator content will lead to an increase in the shrinkage rate, affecting the shrinkage resistance of bone cement. In Comparative Example 11, the bone cement without the addition of nano-microcrystalline cellulose silver filler has the highest shrinkage rate, indicating that its nano-microcrystalline cellulose silver filler can effectively affect the migration of free radicals, thereby indirectly affecting the shrinkage rate. The shrinkage rate of Comparative Example 9 increases, and the compressive strength and flexural strength both decrease. The shrinkage rate of Comparative Example 10 decreases, but the compressive strength and flexural strength are the lowest. When the content of nano-microcrystalline cellulose silver filler is higher than 0.3%, it is difficult to avoid the agglomeration between nanomaterials, which causes the mechanical properties of bone cement to decrease, resulting in a decrease in compressive strength and flexural strength. It can be seen from Comparative Examples 8 to 11 that the shrinkage rate is not only related to the content of the photoinitiator, but also to the use of the nano-microcrystalline cellulose silver-loaded filler. A certain content of photoinitiator and a certain content of nano-microcrystalline cellulose silver-loaded filler can cooperate with each other to enable the bone cement to maintain a low anti-shrinkage ability and good mechanical properties.
[0186] Experiment 3: In vitro antibacterial performance test
[0187] The antibacterial properties of the bone cements prepared in Example 4 and Comparative Examples 9-11 were tested by the following methods:
[0188] (1) Bacteria culture
[0189] Place multiple layers of medical gauze in the culture dish, sterilize with high temperature and wet heat, and then dry. Perform the test operation on a sterile operating table: Pipette 10mL of PBS buffer onto the gauze to ensure the humidity environment in the culture dish, place the prepared bone cement specimens on the gauze (3 specimens of each type as parallel controls), and pipette 10μL of the prepared Staphylococcus aureus liquid on the surface of each specimen and apply it evenly. Place the culture dish with the liquid applied in a 37℃ incubator for 24h.
[0190] (2) Determination of Staphylococcus aureus concentration on the surface of the specimen
[0191] After 24 hours of incubation, the specimens were taken out individually and placed in 1 mL of PBS buffer and shaken with a vortex mixer for 3 minutes to allow the Staphylococcus aureus on the surface of the resin sheet to fall off and disperse into the solution. The specimens were then diluted step by step, and the plates with the same dilution multiples were photographed.
[0192] Specific results such as Figure 1 As shown, A is Example 4, B is Comparative Example 9, C is Comparative Example 10, and D is Comparative Example 11. It can be seen that the addition of nano-microcrystalline cellulose silver-loaded filler makes the bone cement have a certain antibacterial effect.
[0193] Example 9
[0194] A method for preparing a personalized bone cement-based restoration is specifically performed according to the following steps:
[0195] 1. Accurately scan the damaged area
[0196] Use CT or MR medical imaging technology to scan the patient's part to be repaired. The patient's scan data format is DICOM or JPEG format. The scan data layer thickness should not be greater than 1mm, and 0.1-0.3mm can be preferred. Obtain the patient's scan data, import it into the interactive medical image control system software, calculate the part to be repaired by setting the image data threshold range, obtain the patient's medical morphology, generate a visual three-dimensional model, and mirror the patient's contralateral complete data through the mirror tool in the CAD design software or customize the patient's repair through translation module, rotation module, smooth module, Bohr module, stretching, rotation, etc. at the part to be repaired. The matching degree of the contralateral complete data can be referred to.
[0197] 2. Light-curing 3D printing of bone cement-based restorations
[0198] The image of the part to be repaired obtained in step 1 is converted into the general STL format for 3D printing. The relevant parameters are set according to Table 1. The bone cement prepared in step 1 is used as the printing ink. The laser tracks the layered cross section through computer control and is exposed to the bone cement in the container to solidify the layered cross section. Then, the height of one layer is raised and lowered, and the formed layer is covered by a layer of bone cement. Then a new layer is scanned, and the new solidified layer is firmly attached to the previous layer. Repeat the above steps until the entire restoration model is completed and the restoration of the corresponding part is obtained.
[0199] Table 1
[0200] Printing parameters Reference value Triggering light wavelength 350~450nm Triggering light intensity <![CDATA[150~230mW / cm 2 ]]> Blue light generator moving speed 5~15mm / min Print layer thickness 60~110μm
[0201] 3. Post-processing
[0202] (1) Post-curing: After printing, the bone cement sample is placed in a UV curing box for secondary curing to ensure complete curing. Secondary curing time and conditions: UV light power 100mW / cm 2 , curing time is 10 to 20 minutes.
[0203] 4. Cleaning and drying: After curing is completed, remove the bone cement sample from the printing platform. Use an appropriate solvent (such as ethanol) to clean the sample surface to remove uncured residues. Then place the sample in a drying oven for drying.
[0204] Application Examples
[0205] The bone cement prepared in Example 4 is selected to customize a personalized bone cement-based restoration for the patient's repaired part according to the preparation method provided in Example 9. Specifically, the following steps are performed:
[0206] 1. Accurately scan the damaged area
[0207] The CT medical imaging technology is used to scan the skull part of the patient to be repaired. The patient scan data format is DICOM format, and the scan data layer thickness is 0.5 mm. The patient scan data is obtained and imported into the interactive medical image control system software (MimicsInnovation Suite 22). The part to be repaired is calculated by setting the image data threshold range (the threshold range is between 226 and 3071), the patient's medical morphology is obtained, and a visual three-dimensional model is generated. In the CAD design software, the patient's contralateral complete data is mirrored by the mirror tool or customized by the translation module, rotation module, smooth module, Bohr module, stretching, rotation, etc. at the part to be repaired. The matching degree of the contralateral complete data can be referred to.
[0208] 2. Light-curing 3D printing of bone cement-based restorations
[0209] The image of the part to be repaired obtained in step 1 is converted into the general STL format for 3D printing, and the relevant parameters are set according to Table 2. The bone cement prepared in step 1 is used as the printing ink. The laser tracks the layered cross section through computer control and is exposed to the bone cement in the container to solidify the layered cross section. Then, the height of one layer is raised and lowered, and the formed layer is covered by a layer of bone cement. Then a new layer is scanned, and the new solidified layer is firmly attached to the previous layer. Repeat the above steps until the entire restoration model is completed and the restoration of the corresponding part is obtained.
[0210] Table 2
[0211] Printing parameters Reference value Triggering light wavelength 405nm Triggering light intensity <![CDATA[200mW / cm 2 ]]> Blue light generator moving speed 10mm / min Print layer thickness 100μm
[0212] 3. Post-processing
[0213] (1) Post-curing: After printing, the bone cement sample is placed in a UV curing box for secondary curing to ensure complete curing. Secondary curing time and conditions: UV light power 100mW / cm 2 , curing time 30 minutes.
[0214] 4. Cleaning and drying: After curing is completed, remove the bone cement sample from the printing platform. Use ethanol to clean the sample surface to remove uncured residues. Then place the sample in a drying oven for drying.
[0215] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a nano-microcrystalline cellulose silver-loaded filler, characterized in that: The following steps are involved: A1. Pre-treating microcrystalline cellulose by adding microcrystalline cellulose to an acid solution to obtain a microcrystalline cellulose dispersion, dialyzing the microcrystalline cellulose dispersion, and freeze-drying the dialyzate to obtain nano-microcrystalline cellulose; A2. Add nano-microcrystalline cellulose to the dopamine solution, mix well, slowly add the silver ammonia solution, add an excess amount of reducing agent, and stir to obtain the nano-microcrystalline cellulose silver-loaded filler.
2. The preparation method according to claim 1, characterized in that: The amount of microcrystalline cellulose added is 4 to 6 g of microcrystalline cellulose per 40 to 50 ml of acid solution, preferably 5 g of microcrystalline cellulose per 45 ml of acid solution; Preferably, the concentration of the acid solution is 50-80wt.%, preferably 65wt.%; Preferably, the acid solution comprises an aqueous solution of sulfuric acid, hydrochloric acid, acetic acid, citric acid or nitric acid; Preferably, the pretreatment comprises reacting at a temperature of 50 to 60°C for 3 to 7 hours, preferably at 55°C for 5 hours; Preferably, the pretreatment further comprises adding distilled water after the reaction until the pH of the solution is neutral, and then cooling and ultrasonicating to obtain a microcrystalline cellulose dispersion; Preferably, the ultrasonic conditions include ultrasonication at a power of 230 to 280 W for 12 to 18 min; preferably ultrasonication at a power of 250 W for 15 min; Preferably, the pretreatment further comprises centrifuging to remove the supernatant, and washing the precipitate with distilled water 2 to 3 times; Preferably, the centrifugation condition is 3000 rpm to 6500 rpm for 5 to 30 min, preferably 5000 rpm for 5 to 30 min; Preferably, the dialysis comprises dialysis until the pH of the dialysate is neutral; Preferably, the pore size of the dialysis membrane is 3500-7000Da, preferably 3500Da; Preferably, the freeze-drying temperature is -30 to 0°C, preferably -20°C.
3. The preparation method according to claim 1, characterized in that: The mixing ratio of the nano-microcrystalline cellulose to the dopamine solution is 0.5-5:100 (w / v), preferably 1:100; Preferably, the dopamine solution is prepared by adding dopamine hydrochloride into a buffer solution; Preferably, the concentration of dopamine hydrochloride is 1 to 5 mg / ml, preferably 2 mg / mL; Preferably, the buffer is Tris-HCl buffer or PBS buffer; Preferably, the volume ratio of the amount of the added silver ammonia solution to the dopamine solution is 0.5 to 3:100, preferably 1:100; Preferably, the silver ammonia solution is prepared by slowly adding concentrated ammonia water to a silver nitrate solution; Preferably, the concentration of the silver nitrate solution is 5 to 30 mM, preferably 10 mM; Preferably, the reducing agent comprises glucose, ascorbic acid or citric acid, preferably glucose; Preferably, the stirring time is 6 to 10 hours, preferably 8 hours.
4. A nano-microcrystalline cellulose silver-loaded filler, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 3.
5. A bone cement for 3D printing, characterized in that: The following components are included in mass percentage: The nano-microcrystalline cellulose silver-loaded filler is prepared by the preparation method according to any one of claims 1 to 3.
6. The bone cement according to claim 5, characterized in that The photoinitiator includes photoinitiator 819, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide or acylphosphonic acid lithium salt; Preferably, the diluent comprises methyl methacrylate, bisphenol A acrylate or glyceryl trimethyl acrylate; Preferably, the cross-linking agent is ethylene glycol dimethacrylate; Preferably, the stabilizer is butylated hydroxytoluene; Preferably, the developer is barium sulfate.
7. The method for preparing bone cement according to claim 5 or 6, characterized in that: The following steps are involved: B1, sequentially mixing polymethyl methacrylate, a photoinitiator, a diluent, a crosslinking agent, a stabilizer and a developer to obtain a preliminary mixture; B2, adding nano-microcrystalline cellulose silver-loaded filler to the preliminary mixture, and obtaining bone cement by ultrasonication; Preferably, the ultrasonic treatment conditions include 280-320W ultrasonic treatment for 25-35 min, preferably 300W ultrasonic treatment for 30 min.
8. Use of the bone cement according to claim 5 or 6 or the bone cement prepared by the preparation method according to claim 7 in preparing a bone cement-based restoration; Preferably, the bone cement restoration comprises a restoration of a damaged or diseased bone or joint.
9. A method for preparing a personalized bone cement-based restoration, characterized in that: The following steps are involved: C1. Establish a visual 3D negative model based on the data of the part to be repaired; C2. Using the bone cement described in claim 4 or 5 or the bone cement prepared by the preparation method described in claim 6 or 7, 3D printing is performed based on a negative mold of a visualized three-dimensional model to obtain a personalized bone cement-based restoration.
10. The preparation method according to claim 9, characterized in that: The step C1 comprises the following steps: C11. Perform CT scan or MR scan on the part to be repaired to obtain scan data; C12. Calculate the medical morphology of the part to be repaired by interactive medical image control system software, and obtain a visualized three-dimensional model of the part to be repaired; C13, obtaining a negative model of the visualized three-dimensional model of the part to be repaired according to the visualized three-dimensional model CT of the part to be repaired; Preferably, the layer thickness of the scan data is ≤1 mm, preferably 0.1 to 0.3 mm; Preferably, the inner surface of the female mold of the visualized three-dimensional model is provided with concave and convex patterns with a depth of 0.1 to 1.5 mm; Preferably, after step C12, the step further includes comparing the visualized three-dimensional model of the part to be repaired with the visualized three-dimensional model of the opposite side of the part to be repaired, and if there is asymmetry, making corrections according to the visualized three-dimensional model of the opposite side of the part to be repaired; Preferably, the initiating light wavelength of the 3D printing is 350-450nm, preferably 405nm; Preferably, the triggering light intensity of the 3D printing is 150-230 mW / cm 2 , preferably 200mW / cm 2 ; Preferably, the moving speed of the blue light generator for 3D printing is 5 to 15 mm / min, preferably 10 mm / min; Preferably, the thickness of the printing layer of the 3D printing is 60-110 μm, preferably 100 μm; Preferably, the step B2 further includes secondary curing and cleaning and drying; Preferably, the secondary curing comprises ultraviolet light irradiation for 10 to 20 minutes; Preferably, the power of the ultraviolet light irradiation is 90-120 mW / cm 2 , preferably 100 mW / cm 2 ; Preferably, the cleaning comprises cleaning the surface using an organic solvent; Preferably, the organic solvent comprises ethanol solution, acetone or ethylene glycol diacetate.